Coloring Competition as an Inclusive Education Tool to Train Elementary School Students' Creativity - Nur Wahyuni (Outline Journal of Community Development, 2024)
Through a coloring competition with normal children and ABK participants, the aim is to provide participants with knowledge about inclusive education in formal schools for children with special needs. Children's growth and development involves the development of fine motor skills and creativity. Coloring competitions are effective in practicing this skill, helping children understand the concept of color, increasing concentration, and growing self-confidence. Creativity needs to be fostered from an early age, and coloring competitions can encourage children to be more productive, confident and develop their potential. Battuta University's community service in Manhattan Times Square, Medan, involved a coloring competition for 50 elementary school students aged 5-9 years. This activity includes preparations such as choosing a theme, jury and location, as well as holding competitions, delivering material and entertainment.